2020
DOI: 10.1097/cm9.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of fatal and recovered cases of coronavirus disease 2019 in Wuhan, China: a retrospective study

Abstract: Background: The 2019 novel coronavirus has caused the outbreak of the acute respiratory disease in Wuhan, Hubei Province of China since December 2019. This study was performed to analyze the clinical characteristics of patients who succumbed to and who recovered from 2019 novel coronavirus disease (COVID-19). Methods: Clinical data were collected from two tertiary hospitals in Wuhan. A retrospective investigation was conducted to analyze the clinical characteristics of fatal cases of COVID-19 (death group) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
680
5
29

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(761 citation statements)
references
References 29 publications
47
680
5
29
Order By: Relevance
“…Increasing number of reports and clinical observations demonstrate that patients infected with SARS-CoV-2 present not only respiratory signs of infection but also diarrhoea, vomiting, nausea or abdominal pain. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed ground-glass opacities in CT scan and was afterwards tested positive from nasopharyngeal swab. 22 Interestingly, the first described case of COVID-19 in United…”
Section: Covid-19 and Gastrointestinal Tractmentioning
confidence: 99%
“…Increasing number of reports and clinical observations demonstrate that patients infected with SARS-CoV-2 present not only respiratory signs of infection but also diarrhoea, vomiting, nausea or abdominal pain. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed ground-glass opacities in CT scan and was afterwards tested positive from nasopharyngeal swab. 22 Interestingly, the first described case of COVID-19 in United…”
Section: Covid-19 and Gastrointestinal Tractmentioning
confidence: 99%
“…SARS, MERS and COVID-19 can cause intestinal, respiratory, neuronal and hepatic diseases, and may lead to respiratory distress syndrome, organ failure, and even death in severe cases [5][6][7] . Several studies have reported the clinical characteristics and laboratory findings associated with different degrees of liver injury in patients with COVID-19 infection [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . We are aware of no meta-analysis that summarized available findings in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…(58)ThrombosisOne of the prominent findings replicated across most early studies of COVID-19 includes disarray of the coagulation and fibrinolytic system. Hospitalized patients with moderate and severe COVID-19 and those with poorer outcomes are noted to have prolonged prothrombin time (PT), elevated D-dimer, and activated partial thromboplastin time (APTT) (35,53,54,64). In the context of a clinical picture that is consistent with disseminated intravascular thrombosis, it is reasonable to speculate that COVID-19 would be associated with venous or arterial thrombi, however the incidence has not been published.…”
mentioning
confidence: 99%